Exploring the biocontrol potential of soil bacteria isolated from North Sumatra, Indonesia, against pathogenic fungi - SRI WAHYUNI; DWI SURYANTO; KIKI NURTJAHJA (Society for Indonesian Biodiversity, 2025)
Abstract. Wahyuni S, Suryanto D, Nurtjahja K. 2025. Exploring the biocontrol potential of soil bacteria isolated from North Sumatra, Indonesia, against pathogenic fungi. Biodiversitas 26: 2039-2050. The diversity of soil bacteria is very important in the ecosystem. Bacteria can function as biological control agents by exhibiting antagonistic activities and producing bioactive metabolite compounds that inhibit the growth of plant pathogens. This study aimed to determine the characteristics of various bacteria, test their pathogenicity, and inventory the production of metabolite compounds produced by these bacteria. Bacteria were isolated from soil sources of wood plant areas, bamboo, and agriculture in the Sibolangit area, North Sumatra, Indonesia. Various tests were carried out to obtain the morphological and biochemical characteristics of the isolates obtained, such as macroscopic, staining, triple sugar iron, catalase, starch, gelatin, and Gram. This research showed 20 isolates that could control pathogens with the highest inhibition value, namely isolate B6 with an inhibition value on Fusarium sp. (32.42 mm) and on Colletotrichum sp. (20.72 mm). Isolate SP1 showed an inhibition value on Aspergillus niger (28.32 mm), Aspergillus flavus (25.12 mm), Fusarium sp. (23.11 mm), and Colletotrichum sp. (20.23 mm). Identification of other metabolite compounds isolates B3, T4, and SP10 were able to dissolve phosphate, with inhibition zones of 15.2 mm, 14.3 mm, and 7.1 mm; chitinase activity was produced by species B6 with an inhibition zone of 10.3 mm, and IAA hormone activity was obtained with the highest concentration of 12.86 ppm and the lowest 2.89 ppm. Of the several bacterial isolates treated, species B6 and SP1 have good potential to be developed as biological control agents. Utilizing local natural resources is very important because local soil microorganisms have adapted to the environment and have a unique potential to fight pathogens.